Deaths in young people after contact with the youth justice system: a retrospective data linkage study. (2018) - Kinner, Stuart; Tibble, Holly; Hail-Jares, Katie; Borschmann, Rohan; Spittal, Matthew; Clough, Alan; Sawyer, Susan; Miller, Adrian; Cadet-James, Yvonne
No abstract available